The impact of logging roads on dung beetle assemblages in a tropical rainforest reserve. (January 2017) - Edwards, Felicity A.; Finan, Jessica; Graham, Lucy K.; Larsen, Trond H.; Wilcove, David S.; Hsu, Wayne W.; Chey, V.K.; Hamer, Keith C.
Abstract: The demand for timber products is facilitating the degradation and opening up of large areas of intact habitats rich in biodiversity. Logging creates an extensive network of access roads within the forest, yet these are commonly ignored or excluded when assessing impacts of logging on forest biodiversity. Here we determine the impact of these roads on the overall condition of selectively logged forests in Borneo, Southeast Asia. Focusing on dung beetles along > 40 km logging roads we determine: (i) the magnitude and extent of edge effects alongside logging roads; (ii) whether vegetation characteristics can explain patterns in dung beetle communities, and; (iii) how the inclusion of road edge forest impacts dung beetle assemblages within the overall logged landscape. We found that while vegetation structure was significantly affected up to 34 m from the road edge, impacts on dung beetle communities penetrated much further and were discernible up to 170 m into the forest interior. We found larger species and particularly tunnelling species responded more than other functional groups which were also influenced by micro-habitat variation. We provide important new insights into the long-term ecological impacts of tropical logging. We also support calls for improved logging road design both during and after timber extraction to conserve more effectively biodiversity in production forests, for instance, by considering the minimum volume of timber, per unit length of logging road needed to justify road construction. In particular, we suggest that governments and certification bodies need to highlight more clearly the biodiversity and environmental impacts of logging roads. Highlights: Distinct edge effects along roads penetrate > 100 m into the logged forest interior. Vegetation changes however, differed within a maximum of 34 m of the road edge. Large diurnal, and tunnelling dung beetles are affected more by proximity to roads. Micro-habitat variations shown to influence large tunnelling species.